Quivers and Three-Dimensional Lie Algebras - Pike, Jeffrey (Université d'Ottawa / University of Ottawa, 2015)
We study a family of three-dimensional Lie algebras that depend on a continuous parameter. We introduce certain quivers and prove that idempotented versions of the enveloping algebras of the Lie algebras are isomorphic to the path algebras of these quivers modulo certain ideals in the case that the free parameter is rational and non-rational, respectively. We then show how the representation theory of the introduced quivers can be related to the representation theory of quivers of affine type A, and use this relationship to study representations of the family of Lie algebras of interest. In particular, though it is known that this particular family of Lie algebras consists of algebras of wild representation type, we show that if we impose certain restrictions on weight decompositions, we obtain full subcategories of the category of representations that are of finite or tame representation type.
Keywords: Algebra; Lie algebra; Representation; Quiver